2020
DOI: 10.1111/dth.13747
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mechanical characterization of hyaluronic acid hydrogel cross‐linked with polyethylen glycol and its use in dermatology

Abstract: Hydrogels based on hyaluronic acid are used to restore volume, hydration, and skin tone, as well as to correct scars, asymmetries or defects of the soft tissue. Hyaluronic acid is often chemically crosslinked with different crosslinking agents in order to improve its mechanical and biological properties. Here we focused on defining the chemical and mechanical characterization of a new hydrogel with specific characteristics: hyaluronic acid polyethylene glycol (PEG)‐crosslinked with a high concentration of hyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…These results were related to the degree of chemical crosslinking between the −OH groups of GG and carbonyl groups of PMVE-MAn which had hardened the hydrogel structure. This result is consistent with the results of other research in this area [38][39][40][41].…”
Section: Mechanical Characterizationsupporting
confidence: 93%
“…These results were related to the degree of chemical crosslinking between the −OH groups of GG and carbonyl groups of PMVE-MAn which had hardened the hydrogel structure. This result is consistent with the results of other research in this area [38][39][40][41].…”
Section: Mechanical Characterizationsupporting
confidence: 93%
“…Zerbinati et al evaluated chemical and mechanical characterization of PEGylated HA filler and the result of their study suggested PEGylated HA has a great bio integration, great chemical, and mechanical properties, compared to other products present on the market cross-linked with other agent instead of PEG [12]. Moreover, Zerbinati et al, in another study, analyzed the safety and biocompatibility of PEGylated HA filler: They concluded that safety and biocompatibility properties are related to an HA produced by genetically modified Bacillus subtilis carrying the gene encoding the enzyme hyaluronic acid synthase (deriving from S. equisimilis genome), and further enhanced by the combined use of PEG [24]. Another important issue arisen is related to the long-lasting effect of these fillers: Zerbinati et al in their study performed several punch biopsies in previously injected areas, 8 months earlier, and noted the filler harmoniously integrated with the structures inside the connective tissue, as collagen fibers, blood, and lymphatic vessels, glands and nerves [11], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds are widely used in medical products (they sustain the content of drugs in systemic fluids by inhibiting their metabolism or protecting the drug from immune degradation), cosmetics and household products (eg, creams and lotions, shampoos, hair dyes, and oral hygiene products) and HA fillers (Neauvia, MatexLab SA, Lugano, CH). 76,77 Positive results of patch tests with propylene glycol at the concentrations of 5%, 10% and 20% were demonstrated in data obtained at Mayo Clinic. It was claimed that it might lead to allergic reactions and irritation.…”
Section: Adverse Reactions To Hyaluronic Fillers and The Sars-cov-2 Epidemicmentioning
confidence: 98%